Transport and Biotransformation of Gliclazide and the Effect of Deoxycholic Acid in a Probiotic Bacteria Model - Ðanić, Maja; Stanimirov, Bojan; Pavlović, Nebojša; Vukmirović, Saša; Lazić, Jelena; Al-Salami, Hani; Mikov, Momir (Frontiers in Pharmacology, 2019)
Introduction: Inter-individual differences in gut microflora composition may affect drug metabolism and overall therapeutic response. Gliclazide is a drug characterized by large inter-individual differences in therapeutic response; however, the causes of these differences are not fully explained and may be the outcome of microbial biotransformation. Recently, great attention has been paid to studies on bile acid (BA) interactions with gut microflora and the role of BAs in the modification of drug transport through biological membranes. The aim: Considering the assumption of gliclazide-probiotic-BAs interactions, the aim of the study was to investigate the transport and biotransformation of gliclazide in probiotic bacteria, as well as the effects of deoxycholic acid (DCA) on gliclazide transport into bacterial cells. Materials and methods: Probiotics were incubated with gliclazide with or without DCA for 24 hours at 37°C. The intracellular and extracellular concentrations of gliclazide were determined at seven time points by high-performance liquid chromatography. Gliclazide biotransformation by the enzymatic activity of probiotic bacteria was examined using appropriate software packages. Results: During the 24 hour incubation with probiotic bacteria, significantly lower extracellular concentrations of gliclazide were observed at all time points compared to controls, while in the group with DCA, the decrease in concentration was noticed only at 24 hours. The total concentration of gliclazide throughout the whole period was significantly lower compared to control. Proposed pathways of gliclazide biotransformation by probiotic bacteria involve reactions of hydrolysis and hydroxylation. Conclusion: Based on the results obtained, it can be concluded that there are interactions of gliclazide-probiotics-DCA, at both the level of active and passive transport into the cells, and at the level of drug biotransformation by enzymatic activity of probiotic bacteria. The effect of these interactions on the final therapeutic response of gliclazide should be further studied and confirmed in in vivo conditions.